ISLAMIC PSYCHOTERAPHY AS A MEANS OF ADOLESCENT EDUCATION IN THE DISRUPTIVE ERA - Suroyya, Naharin - (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2019)
This paper uses the perspective of Islamic psychotherapy examine the development of science and technology in its influence on the changes in adolescent life based on the values of the Qur?an and the Hadith. This research was conducted at MTs Negeri 4 Tulungagung by making student learning activities as the object of research studies. Islamic education is carried out with a spirituality approach through pray, exemplary, patience and sincerity, motivating advice and supervision. Islamic psychotherapy teaches ways to manage mind, verbal, heart and morals of adolescents from physical and spiritual illnesses thatcan be detrimental. First, read the Qur?an as an obligatory routine. Second, prayers in congregation and sunnah prayers. Third, creating a religious and knowledgeable environment. Fourth, fasting Monday and Thursday. This method can develop adolescents to be devoted and knowledgeable man beings, so that adolescents are able to maintain self-integrity, integrity of the soul and achieve self-actualization well.